Environmental determinants of industrial development in transforming Poland - BURCHARD-DZIUBIŃSKA, Małgorzata (European Spatial Research and Policy, 2025)
This report contains a synthesis of studies which were focused on ecological aspects of the restructuring of Polish industry during the recent period. The studies covered the macro-, mezo-, and microeconomic level and they aimed at discribing various determinants and effectiveness of the ecological policy. Due to the fact that a predominant part of all air, water and soil pollutants are of industrial origin, it is in a broadly understood restructuring of industry that ways of solving the problems arising at the intersection of economy and natural environment should be sought. The transformation should encompass both the branch structure and the commodity structure of industry. The period of systemie transformation witnessed by Poland those days has aroused hopes for a joint solution of economic and ecological problems. The present report is an attermpt to answer the question whether these expcctations can come true.